808 nm-triggered optical thermometry based on up-conversion luminescence of Nd3+/Yb3+/Er3+ doped MIn2O4 (M = Ca, Sr and Ba) phosphors. Issue 19 (30th April 2018) - Liu, Xue; Li, Ting; Zhao, Xiaoqi; Suo, Hao; Zhang, Zhiyu; Zhao, Puju; Gao, Shuai; Niu, Mu
Abstract : 808 nm driven UCL mechanism and intrinsic structure-dependent optical thermometric performance of MIn2 O4 :Nd 3+ /Yb 3+ /Er 3+ (M = Ca, Sr, and Ba) are elucidated. Abstract : Optical thermometry based on up-conversion (UC) fluorescent intensity ratio (FIR) with 808 nm excitation is preferable in water-rich environments, and investigation of the ambiguous intrinsic influencing factors on host-dependent sensitivity is a prerequisite for the development of highly sensitive thermometry. Herein, MIn2 O4 :Nd 3+ /Yb 3+ /Er 3+ (M = Ca, Sr, and Ba) microcrystals with low phonon energy are synthesized via a sol–gel method. Intense UC luminescence with tunable emission color from green to red is obtained by controlling the Yb 3+ content, and the UC mechanisms and successive energy transfer of Nd 3+ → Yb 3+ → Er 3+ are elaborated using lifetime measurements. The thermal sensing properties of the samples based on the thermally coupled levels ( 4 S3/2 / 2 H11/2 ) of Er 3+ are assessed, and their sensitivities increase gradually with an increase in temperature and reach the maximum of about 0.0048, 0.0033 and 0.0058 K −1 at 490 K for M = Ca, Sr, and Ba, respectively. By analysing the host structure, site symmetry of M 2+ ions and characteristics of the M–O bonds, it is proposed that the higher Ca–O bond covalency in CaIn2 O4 leads to better sensitivity than SrIn2 O4 with the same structure, and the optimal sensitivity in BaIn2 O4 is mainly attributed to the specific local crystal field of the Ba 2+ site with higher ligancy and longer chemical bonds. These results provide insight for the selection of appropriate matrix materials to achieve higher temperature detection sensitivity.